Effect of Methods of sowing mulching and irrigation on wheat and Gram Crop - Mourya, B.M.; Yadav, R.D. (Journal of Soil and Water Conservation, 2022)
Experiment on methods of sowing •mulching and irrigation on wheat and gram crop was undertaken at Agricultural Research Farm Powarkheda during rabi season of 1996-97 and 1997-98. Results indicated that grain yield and benefit cost ratio was maximum in regular line sowing as compared to border method of sowing in both the crop. Irrigation at 31st day stage of wheat crop and 45th day stage of gram crop was found effective as it increased the grain yield and benefits cost ratio. Mulching through soybean straw @ 4 t/ha at well establishment of wheat crop was found effective which increased they yield by 8% over no mulch. Mulching by soybean straw in gram was found teletoxic as it reduced the grain yield by 8-9% in gram crop.